The evolution of morphological novelty - Patel, Nipam (Henry Stewart Talks, 2008)
Role of homeotic (Hox) genes in morphological evolution, Arthropod evolution, Crustacean appendages, The role of gene regulation in evolution
Reviewed at 2018/05/31